2014
DOI: 10.1159/000365278
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Cardiac Output Monitoring in Preterm Infants Undergoing Patent Ductus Arteriosus Ligation: A Comparison with Echocardiography

Abstract: Background: Non-invasive cardiac output monitoring (NICOM; NICOM™) may be useful in the management of extremely premature preterm infants. Objectives: To evaluate a new bioreactance-based method of continuous NICOM in preterm infants following patent ductus arteriosus (PDA) ligation. Methods: Infants underwent three paired NICOM and echocardiography assessments of stroke volume (SV) and left ventricular output (LVO) in the postoperative period: at 1, 6-8, and 16-18 h postoperatively. NICOM- and echocardiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 20 publications
4
30
0
Order By: Relevance
“…Whereas CO gradually improved by 24 h post ligation, the postoperative increase in SVR was sustained throughout the study period. Although this study performed intermittent rather than continuous hemodynamic assessments due to the use of oscillometric blood pressure measurements, their observations are consistent with the findings reported by Weisz et al [64]. Both of these studies also highlight the importance of further efforts to validate non-invasive CO monitoring systems in neonates and that caution should be used when interpreting the measurements obtained by the use of the novel technologies alone.…”
Section: Computational Modeling From Research To Patient Caresupporting
confidence: 90%
See 1 more Smart Citation
“…Whereas CO gradually improved by 24 h post ligation, the postoperative increase in SVR was sustained throughout the study period. Although this study performed intermittent rather than continuous hemodynamic assessments due to the use of oscillometric blood pressure measurements, their observations are consistent with the findings reported by Weisz et al [64]. Both of these studies also highlight the importance of further efforts to validate non-invasive CO monitoring systems in neonates and that caution should be used when interpreting the measurements obtained by the use of the novel technologies alone.…”
Section: Computational Modeling From Research To Patient Caresupporting
confidence: 90%
“…Weisz et al [64] studied postoperative CO changes in extremely premature infants after PDA ligation using echocardiography and a non-invasive CO-monitoring system based on thoracic bioreactance (NICOM) [27]. Based on high versus low LVO at 1 h after ligation, the authors identified two groups of patients.…”
Section: Computational Modeling From Research To Patient Carementioning
confidence: 99%
“…Various approaches include interpretation of pulse oximetry information (perfusion index, plethysmography), (19)(20)(21) interpretation of transthoracic electrical signals (impedance, cardiometry, velocimetry, bioreactance), (22)(23)(24)(25) regional oxygenation (near-infrared spectroscopy), (26) alterations in skin microcirculation (side stream dark-field imaging, reflectance spectrophotometry), (27)(28) resonance Raman spectroscopy (Lauren J. Ruoss, personal communication, May 2018), and others.…”
Section: Diagnosismentioning
confidence: 99%
“…32 Using bioreactance to continuously monitor cardiac output postligation, milrinone monotherapy for postoperative LVO less than 200 ml/min/kg has been shown to be associated with recovery of LVO. 34 In a retrospective cohort of neonates with low LVO 1-hour postligation, treatment with prophylactic milrinone was associated with improved LVO and tissue Doppler systolic velocities in the lateral and septal wall, with no significant effects on diastolic markers. 31 This suggests that the primary mechanism of action is related to improved systolic function with afterload reduction rather than lusitropy.…”
Section: Targ E Ted Neonatal Echoc Ardiog R Aphy G Uided P Os Topermentioning
confidence: 89%